An Overview of Criminal Provisions Responding to Hate Speech in Turkish Law - Aydın, Devrim (Journal of Legal Studies, 2023)
There are several reports and cases that demonstrate the clear increase of hate speech in Turkey through media and especially on social media against some national and religious minorities, asylum seekers, refugees, and LGBTQ. This was also reported by the European Commission which pointed out that there is no effective prosecution of incitement to hatred, including by the media. In addition hate speech is not clearly regulated, expressions that can be considered hate speech are interpreted sometimes through provisions that regulate the crime of defamation against a person or the crime of defamation against a part of people. Although tidy legislation which defines and regulates hate speech through media, the internet and, social media is not yet available in the Turkish Penal Code. Major provisions that can be associated with hate speech are available in the Turkish Penal Code in a scattered manner. There are also related regulations in the law governing internet broadcasting and the law governing radio and television broadcasting. Expressions that can be considered hate speech are, in some cases interpreted through provisions that regulate the crime of defamation against the person. The most important problem pertains to the fact that hate speech and hate crimes have not been prescribed under a single title in Turkish Law.